Impact of Foreign Direct Investment on Domestic Innovations In Developing Economies: Moderating Role of Country-Level Governance - Shamsub, Hannarong (Innovation Journal of Social Sciences and Economic Review, 2023)
The study aims to explore whether country-level governance moderates the relationship between foreign direct investment (FDI) and innovation in developing economies, extending beyond the typical examination of FDI's direct impact on innovation. Utilizing panel data from the World Bank Development Indicators and Worldwide Governance Indicators databases, covering 55 developing countries over a 25-year period from 1995 to 2019, the study employs a Generalized Method of Moments (GMM) system to estimate the moderating effects of governance on the FDI-innovation relationship. The analysis reveals that three of the six governance variables—political stability, the rule of law, and voice and accountability—significantly moderate the impact of FDI on innovation. Specifically, these governance factors amplify the positive effects of FDI on local innovation, indicating that improvements in governance quality enhance the benefits of FDI for innovation in developing countries. The findings suggest that traditional policy measures, such as increasing government expenditure on R&D and education to boost FDI's innovation spillovers, may be inadequate without concurrent improvements in governance quality. Strengthening governance, particularly in the areas of political stability, the rule of law, and voice and accountability, is crucial for maximizing the innovation benefits of FDI in developing economies. Policymakers in developing countries should prioritize enhancing governance quality to fully leverage the innovation potential of FDI. The study highlights the importance of political stability, the rule of law, and voice and accountability in fostering an environment where FDI can effectively contribute to local innovation. Future research should investigate the potential mediating effects of governance variables to provide a more comprehensive understanding of their role in the FDI-innovation nexus.
Keywords: Foreign Direct Investment; Country-Level Governance; Governance; Innovation; Developing economies